Estudo comparativo do ácido tranexâmico no pré-hospitalar e sala de emergência: impacto em pacientes de trauma com choque hemorrágico - Lima, Daniel Souza (2023)
Introduction: patients who suffered trauma with hemorrhagic shock have shown early coagulation disorders, identified since they enter the emergency room, which are related to mortality outcomes. These findings lead to clinical research for its early administration, still in pre-hospital care (PHC), of an antifibrinolytic agent -- tranexamic acid (TXA). Objectives: to assess the effects of pre-hospital use of TXA to treat hemorrhagic shock caused by trauma on mortality and parameters related to hemorrhagic shock, coagulopathy, transfusion, and to identify mortality-associated variables. Methods: this is a retrospective cohort study which compares two cohorts, one of which is a group with pre-hospital care patients who were administered TXA in the 192 Fortaleza Mobile Emergency Care Service, and a control group which took the first TXA dose in the emergency department of Dr. José Frota Institute Hospital (IJF). All cases observed had patients who received transfusion through the activation massive transfusion protocol (MTP). Results: patients in the pre-hospital care group were more severe (Injury Severity Score 19.07±6.18 vs 24.20±8.67, p=0.002), although there was no difference in 30-mortality rates between the groups (39.0% vs 38.8%, p=0.981). Early mortality (within 24 hours) also had no difference between groups (14.6% vs 14.3%, p=0.963). The rate of trauma-induced coagulopathy (TIC), characterized by INR > 1.5 upon entry, was 20.7%, and was associated with a larger amount of transfusion of RBC concentrate (5.00±2.37 versus 3.34±1.86, p=0.003). In multivariate analysis, ionized calcium ≤1.15 mmol/l upon entry and pre-hospital intubation were mortality-predictor variables. Conclusion: severely-ill patients with traumatic hemorrhagic shock who received an initial dose of TXA in PHC, even if showing higher severity scores, had a survival rate similar to those in the control group, which suggests a potential benefit of this antifibrinolytic agent in patients with this profile.